Mouse Models of C9orf72 Hexanucleotide Repeat Expansion in Amyotrophic Lateral Sclerosis/ Frontotemporal Dementia - Batra, Ranjan; Lee, Chris W. (Frontiers in Cellular Neuroscience, 2017)
The presence of hexanucleotide repeat expansion (HRE) in the first intron of the human C9orf72 gene is the most common genetic cause underlying both familial amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Studies aimed at elucidating the pathogenic mechanisms associated of C9orf72 FTD and ALS (C9FTD/ALS) have focused on the hypothesis of RNA and protein toxic gain-of-function models, including formation of nuclear RNA foci containing GGGGCC (G4C2) HRE, inclusions containing dipeptide repeat proteins through a non-canonical repeat associated non-ATG (RAN) translation mechanism, and on loss-of-function of the C9orf72 protein. Immense effort to elucidate these mechanisms has been put forth and toxic gain-of-function models have especially gained attention. Various mouse models that recapitulate distinct disease-related pathological, functional, and behavioral phenotypes have been generated and characterized. Although these models express the C9orf72 HRE mutation, there are numerous differences among them, including the transgenesis approach to introduce G4C2-repeat DNA, genomic coverage of C9orf72 features in the transgene, G4C2-repeat length after genomic stabilization, spatiotemporal expression profiles of RNA foci and RAN protein aggregates, neuropathological features, and neurodegeneration-related clinical symptoms. This review aims to (1) provide an overview of the key characteristics; (2) provide insights into potential pathological factors contributing to neurotoxicity and clinical phenotypes through systematic comparison of these models.